The Importance of High-Bandwidth Low-Latency Network Systems in the Modern Age - Secara, Ion-Alexandru; Hordiiuk, Dariia (Transactions on Engineering and Computing Sciences, 2023)
This paper investigates the importance of high-bandwidth and low-latency network systems in the modern age. It introduces the concepts of networks systems, bandwidth and latency. Then the paper analyzes factors affecting bandwidth and latency in network systems. The factors analyzed include the distance over which the network connection spans, the router and wireless protocols used, as well as the type of cabling used in wired connections. Finally, the paper uses the aforementioned analysis to investigate the choices and solutions that financial institutions use in order to optimize the speed and capacity of their algorithms, when performing high-frequency trading. Choices analyzed include the proximity of the algorithms to the exchange servers, as well as the type of cabling used in wired connections to facilitate fast data transfers.